1953
DOI: 10.1128/jb.65.2.187-192.1953
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Adaptive Lag of Pseudomonas Fluorescens Toward Citrate

Abstract: During the course of studying the terminal respiration of Pseudomonas fluorescens, detailed adaptive patterns were worked out with particular respect to compounds conceivably con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1957
1957
1975
1975

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 12 publications
(9 reference statements)
1
20
0
Order By: Relevance
“…Citrate transport systems have been indicated for certain Pseudomonas species, by a lag period before oxidation of citrate by intact cells, and by prolongation of the lag period by amino acid analogues, ultraviolet irradiation, and chloramphenicol (Kogut and Podoski, 1953;Barret, Lakon, and Kallio, 1953;Clarke and Meadow, 1959). A similar situation has been shown for Aerobacter aerogenes by Green (Davis, 1956), who found that glucose prevented adaptation to citrate.…”
Section: Discussionmentioning
confidence: 69%
“…Citrate transport systems have been indicated for certain Pseudomonas species, by a lag period before oxidation of citrate by intact cells, and by prolongation of the lag period by amino acid analogues, ultraviolet irradiation, and chloramphenicol (Kogut and Podoski, 1953;Barret, Lakon, and Kallio, 1953;Clarke and Meadow, 1959). A similar situation has been shown for Aerobacter aerogenes by Green (Davis, 1956), who found that glucose prevented adaptation to citrate.…”
Section: Discussionmentioning
confidence: 69%
“…Homogenate-methylene blue reduction demonstrates: a-ketoglutaric, succinic, malic, and lactic dehydrogenases, fumarase, glutamic transaminase, and the absence of glutamic dehydrogenase. Bacteria which also cannot absorb metabolic intermediates metabolize them (4,12,18,20,24). P. caeca produces typical plant amylose and amylopectin( l o ) , Q-enzyme( 3,6,7), and phosphoylase, but lacks hexokinase(33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of adaptive changes in cellular permeability is not new. Such changes have been postulated to explain the adaptation of certain bacteria ( 1,2,9,10) to the oxidation of citrate and other Rrebs cycle intermediates. In these cases, the substrate in question was oxidized slowly, if a t all, by unadapted cells, yet cell-free extracts of unadapted organisms oxidized the same substrate immediately, and as readily as did comparable preparations of adapted cells.…”
Section: Discussionmentioning
confidence: 99%
“…The gullet, or food-passage system, is a partially ciliated tube linking the animal's fluid environment with its cytoplasm. In Corliss' terms ( 1) , the anterior open side of the tube (occupying about half of the tube's length) is the buccal overture. The posterior closed portion is called the buccal cavity.…”
Section: Discussionmentioning
confidence: 99%